2020
DOI: 10.1002/cbin.11486
|View full text |Cite
|
Sign up to set email alerts
|

The negative feedback between miR‐143 and DNMT3A regulates cisplatin resistance in ovarian cancer

Abstract: Emerging evidence suggests that miR‐143 plays an important role in the regulation of tumor sensitivity to chemotherapeutic agents. The study explores the underlying mechanism of miR‐143 in reversing cisplatin resistance in ovarian cancer. The cisplatin‐resistant ovarian cancer cell line A2780/CDDP was induced and established via treating A2780 cells by gradually increasing cisplatin concentrations. The IC50 values of A2780/CDDP and A2780 to cisplatin were 218.10 ± 1.12 and 21.99 ± 1.12 μM, respectively. Quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…MiRNAs have been found to play a crucial role in the regulation of all major cellular functions, including cell proliferation, differentiation, and apoptosis, which are involved in various human diseases [ 4 ]. MiR-143 is widely distributed in mammalian tissues and serves an important role in a number of physiological processes, such as adipocyte and smooth muscle differentiation [ 5 , 6 , 7 ], tumorigenesis suppression [ 8 ], DNA methylation [ 9 , 10 , 11 , 12 ] and development of tissues and organs [ 13 ]. MiR-143 has been reported as a biomarker for the late stages of hepatocellular carcinoma and liver fibrosis [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs have been found to play a crucial role in the regulation of all major cellular functions, including cell proliferation, differentiation, and apoptosis, which are involved in various human diseases [ 4 ]. MiR-143 is widely distributed in mammalian tissues and serves an important role in a number of physiological processes, such as adipocyte and smooth muscle differentiation [ 5 , 6 , 7 ], tumorigenesis suppression [ 8 ], DNA methylation [ 9 , 10 , 11 , 12 ] and development of tissues and organs [ 13 ]. MiR-143 has been reported as a biomarker for the late stages of hepatocellular carcinoma and liver fibrosis [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches have shown that DNMT3a , a DNA methyltransferase contributing to de novo methylation, is a target of miR-143 [ 9 , 10 , 11 , 12 ]. These studies have reported on solid tumors of primary organs other than the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Double negative feedback of miR-29b and DNMT3A/3B promoted OC progression ( 29 ). Feedback between DNMT3A and miR-143 was a critical epigenetic regulator of cisplatin resistance in OCs ( 66 ). WTAP acting as an oncogenic factor promoted OC progression via WTAP-HBS1L/FAM76A axis ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…While these two miRNAs have already been separately linked to EMT or DNMTs regulation in various tumours (32,42), here we assess the importance of the interplay between these factors in the transition, as well as the ability of miR-429 to directly target DNMT3A. Feedback loops between DNMT3A and miRNAs have already been demonstrated in various cancers; the DNMT3A/miR-200c loop has a relevant role during carcinogenesis and progression in gastric cancer (49), while a negative feedback between miR-143 and DNMT3A regulates cisplatin resistance in ovarian cancer (50).…”
Section: Discussionmentioning
confidence: 99%